The isolation and characterisation of a Babesia bovis stock from outbreaks on a farm in the Swartberg region of KwaZulu-Natal, South Africa - Latif, Abdalla A. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.